Children's drawing and telling of the multiple facets of the Greek financial crisis. Issue 1 (1st March 2014) - Christopoulou, Martha
This art-based case study illustrates how primary-age children engaged in a drawing-telling project in order to represent their understandings of the Greek financial crisis. Living in a country where, for the past five years, the topic of financial crisis has vastly permeated television and print media discourse, social networks discussions and adult talk, has raised considerable interest about how primary-age students understand, view and identify this crisis. The children who participated in the research were asked to communicate their understandings of the financial crisis and its effects on Greek society through verbal and visual texts. Descriptions of selected 'drawing and telling' accounts show how these children not only depicted but also manipulated concepts and issues interrelated with the financial crisis as they created and recreated images, texts, ideas and feelings. The findings illustrate these children's understanding, worries and fears and suggest that art education can be a space for healing and recovery from the adversities caused by the financial crisis and a place for fostering resilience.